Desenvolvimento, barbárie e educação ambiental: reprodução comportamentalista ou construção de enfrentamentos para além do capital? Elementos para uma reflexão crítica acerca do Projeto ECOA - SOUSA, Tauan de Almeida (2016)
The study aims to reflect on the possibilities opened up by ECOA Program of Comunity Enviromental Education, realized by agents linked to ALCOA/ALUMAR, developmental project implemented in the São Luís’ Rural area II since the early 1980s. It is being questioned if such initiative act as transmitter of a framework of values that, supposedly, seeks pointing directions in tackling environmental problems, but slips in reproduction of the current scenario of society, or act as a practice that open space for criticism and provide elements to face the logic that produces the problems picture today known as the environmental crisis. São Luís’ Rural area II was chosen ‘cause the region, since the indicated period, it’s a stage of what contemporary sociological literature call as environmental conflicts arising from the implementation of development projects, its consequences, and the permanent invested for allocation new ventures, which live to produce threats to communities and the continuity of their social reproduction, understood both in the physical and symbolic context. To achieve the intent here proposed, the research involved literature review with exploratory nature, document analysis and semi-structured interviews. This thesis has as a backdrop the theoretical discussion about modernity, development, environmental conflicts, sustainability and environmental education. The research concludes that the ECOA Program is part of the group that the literature about the theme describes as conservative Environmental Education. Therefore, as a development, we have the depoliticization of environmental education, as well as the closed of spaces of confrontation of the elements that produces the social and environmental problems and conflicts present currently in the São Luís’ Rural Zone II.